The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1210/en.2018-00836
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal miRNA Profile During Term and Preterm Birth Pregnancies: A Longitudinal Study

Abstract: Despite decades of research in the field of human reproduction, the mechanisms responsible for human parturition still remain elusive. The objective of this study was to describe the changes in the exosomal miRNA concentrations circulating in the maternal plasma between mothers delivering term and preterm neonates, across gestation using a longitudinal study design. This descriptive study identifies the miRNA content in exosomes present in maternal plasma of term and preterm birth (PTB) (n = 20 and n = 10 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 56 publications
3
79
0
1
Order By: Relevance
“…The use of miRNA array analysis has revealed that circulating miRNAs, including miR-302b, miR-548, and miR-1253, are downregulated and that miR-223 is upregulated in plasma from those with spontaneous preterm birth compared to those with normal pregnancy [61]. Moreover, high-throughput sequencing platform results suggest that the miRNA content of circulating exosomes is significantly different in pregnant women with preterm birth or spontaneous preterm labour compared to those with normal pregnancy [40,61,62]. Thus, maternal plasma circulating miRNAs or extracellular vesicle miRNAs can be used to reflect placental pathological changes and as biomarkers to predict preterm birth.…”
Section: Circulating and Exosomal-derived Mirnas In Premature Deliverymentioning
confidence: 99%
“…The use of miRNA array analysis has revealed that circulating miRNAs, including miR-302b, miR-548, and miR-1253, are downregulated and that miR-223 is upregulated in plasma from those with spontaneous preterm birth compared to those with normal pregnancy [61]. Moreover, high-throughput sequencing platform results suggest that the miRNA content of circulating exosomes is significantly different in pregnant women with preterm birth or spontaneous preterm labour compared to those with normal pregnancy [40,61,62]. Thus, maternal plasma circulating miRNAs or extracellular vesicle miRNAs can be used to reflect placental pathological changes and as biomarkers to predict preterm birth.…”
Section: Circulating and Exosomal-derived Mirnas In Premature Deliverymentioning
confidence: 99%
“…One such study demonstrated considerable changes in the plasma-derived exosomal-miRNA profile of human mothers that delivered pre-term compared to those that delivered at term. Increased among the pre-term exosomal miRNA populations were miRNAs involved in glucocorticoid signaling, which is often elevated before labor progression [72]. Even non-EV-derived circulating miRNAs isolated as early as the first trimester can predict pre-term birth [73,74].…”
Section: Disease and Exosomal Mirnasmentioning
confidence: 99%
“…Extracellular vesicles have been suggested as indicators of preterm birth (PTB), with an advantage of non‐invasive isolation from maternal blood and other biological fluids . In a longitudinal study, Menon et al include a cohort of patients with term birth and PTB and reveal a total of 173 miRNAs with significant changes in circulating exosomes across three gestational period by using next‐generation sequencing. The altered miRNAs can be divided into several clusters with different trends of changes over time.…”
Section: Evs As Biomarkers For Pregnancy‐related Diseasesmentioning
confidence: 99%